Effect of periarticular morphine injection for total hip arthroplasty: a randomised, double-blind trial. Issue 3 (May 2019) - Iwakiri, Kentaro; Ohta, Yoichi; Minoda, Yukihide; Kobayashi, Akio; Nakamura, Hiroaki
Background: The periarticular multimodal cocktail injection is currently commonly used to treat postoperative pain after total hip arthroplasty (THA). Despite its analgesic effect, it is frequently reported to cause nausea and vomiting, which are adverse effects of opioids. This study aimed to assess the efficacy of morphine as a component of a multimodal cocktail injection for providing postoperative analgesia and alleviating swelling in patients who underwent THA. Materials and methods: This was a prospective, single-centre, randomised controlled trial involving 100 patients scheduled for unilateral THA. A mixture of steroids, local anaesthetics, NSAIDs, and epinephrine with or without morphine (0.1 mg/kg), was injected into randomly assigned patients. Postoperative assessment was performed with all attending personnel and patients blind to group assignment. Visual analogue scale (VAS) of pain, range of motion (ROM), nausea numerical rating scale (NRS), the total dose of antiemetic drugs used and thigh swelling were compared between groups on postoperative days. Results: Pain VAS scores both at rest and on motion did not differ between the 2 groups at any postoperative time-point. The nausea NRS scores during the postoperative period from 0 minutes to 1 hour and the total dose of antiemetic drugs administered were significantly higher in the morphine group. The thigh girth showed no difference between groups on any of the postoperative days. Conclusions: The results of this study suggested that addition of morphine to the multimodal cocktail injection after THA is not effective for relieving postoperative pain, alleviating swelling, or improving ROM, and results in nausea and vomiting. Randomised controlled trial registration number UMIN000022668.